2020
DOI: 10.1002/cpp.2449
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of depression in first‐episode psychosis: A naturalistic database study

Abstract: Depression is commonly seen in the course of schizophrenia and can occur during any of the phases of the psychotic illness. The present study examines the incidence of depression at baseline and de novo depression in first episode of nonaffective psychoses and the course of depression in the 12 months following first‐episode psychosis, any predictive significance of baseline depression with recurrence of depression in the subsequent phases of the psychotic illness. The study was conducted with a clinical sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…Similarly, Wang et al [11] used an operating characteristic curve and logistic regression analyses and compared the accuracy of clinicians with the accuracy of regression on a standardised scale in terms of evaluating the risk of future suicide attempts in a sample of psychiatric residents. A recent investigation [12] applied multiple logistic regression analyses to identify the socio-demographic and clinical factors associated with depression in a large sample of patients in the context of a first episode psychosis program. The same method was used for identifying the predictors of depression and anxiety in Brazil during the initial outbreak of COVID-19 and it has been observed that females, younger adults, and individuals with fewer children had a higher likelihood of developing depression and anxiety symptoms [13].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wang et al [11] used an operating characteristic curve and logistic regression analyses and compared the accuracy of clinicians with the accuracy of regression on a standardised scale in terms of evaluating the risk of future suicide attempts in a sample of psychiatric residents. A recent investigation [12] applied multiple logistic regression analyses to identify the socio-demographic and clinical factors associated with depression in a large sample of patients in the context of a first episode psychosis program. The same method was used for identifying the predictors of depression and anxiety in Brazil during the initial outbreak of COVID-19 and it has been observed that females, younger adults, and individuals with fewer children had a higher likelihood of developing depression and anxiety symptoms [13].…”
Section: Introductionmentioning
confidence: 99%